PESANTREN ANAK DALAM PERSPEKTIF TEORI ENVIROMENTALISME DAN NATIVISME - Muhammad Aiz (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
This paper aims to find out and analyze the success factors that affect a child's learning process in pesantren. The existence of environmental engineering factors (Enviromentalism) in pesantren and the factor of intelligence from birth (Nativism) owned by each child is the center of study in this article. This research uses a qualitative-descriptive method with a comparative theory approach. The results of this study show that in general (prevalence) between environmental factors and intelligence from birth cannot be separated. Environmental factors will be greatly helped by the intelligence a child has, and vice versa where intelligence needs the right environment to be able to grow and develop optimally. Imam Shafi'i's view representing Muslim scholars does not contradict the views of Locke (Enviromentalism) or Chomsky (Nativism).